Cultural extraterritoriality: Intra-regional politics in contemporary Hong Kong cinema. Issue 3 (1st September 2015) - Fan, Victor
In this article, Victor Fan argues that analysing contemporary Hong Kong cinema requires active rewriting of established postcolonial theories by taking into account the specific mode of colonization of Hong Kong: extraterritoriality. This concept has been responsible for the construction of the cultural plurality, linguistic ambiguity and political liminality of Hong Kong and its cinematographic experience, as well as the incongruence between the community's political consciousness after 1997 and the larger national imagination promulgated by the Beijing government. The term 'extraterritoriality' was translated into Chinese after 1895 via Japanese as 'zhiwai faquan': the right to exercise one's law outside a nation state's sovereign terrain, and colonialism in China between 1844 and 1949 was largely characterized by a continuous reformulation and systematization of this concept. It in fact still informs the way former colonized regions in China are administered today, and the political unconscious of their residents. With Johnnie To's 2012 film Duzhan (Ct. Dukzin)/Drug War as a case study, contemporary Hong Kong cinema, Fan argues, can be understood as a public sphere where an extraterritorial consciousness and the contesting political affects associated with it are actively negotiated.